2013
DOI: 10.5114/aoms.2013.39792
|View full text |Cite
|
Sign up to set email alerts
|

State of the art paper Treatment of non-ST-elevation myocardial infarction and ST-elevation myocardial infarction in patients with chronic kidney disease

Abstract: Renal dysfunction is frequent in patients with non-ST-segment elevation acute coronary syndrome (NSTE-ACS). Chronic kidney disease (CKD) is associated with very poor prognosis and is an independent predictor of early and late mortality and major bleeding in patients with NSTE-ACS. Patients with NSTE-ACS and CKD are still rarely treated according to guidelines. Medical registers reveal that patients with CKD are usually treated with too high doses of antithrombotics, especially anticoagulants and inhibitors of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 72 publications
1
22
0
Order By: Relevance
“…CKD is associated with CVD even in the early stages, and a large number of patients die before developing advanced CKD [26, 5558]. The available data suggest that efforts to reduce mortality in the CKD population should be focused on treatment and prevention of, among others, CAD and congestive heart failure [5861].…”
Section: Lipid Update 2013mentioning
confidence: 99%
“…CKD is associated with CVD even in the early stages, and a large number of patients die before developing advanced CKD [26, 5558]. The available data suggest that efforts to reduce mortality in the CKD population should be focused on treatment and prevention of, among others, CAD and congestive heart failure [5861].…”
Section: Lipid Update 2013mentioning
confidence: 99%
“…1 Despite recognizing this high-risk group, patients with CKD have been largely excluded from randomized controlled trials and management guidelines are not established. 1 ACS diagnosis is based on the clinical presentation of ischemic symptoms, cardiac biomarkers, and electrocardiogram changes. Compared with general population, CKD patients commonly have atypical presentation as in elderly and diabetic; in addition, diagnostic markers have low predictive value since many patients have elevated troponins without having ACS.…”
Section: Introductionmentioning
confidence: 99%
“…Compared with general population, CKD patients commonly have atypical presentation as in elderly and diabetic; in addition, diagnostic markers have low predictive value since many patients have elevated troponins without having ACS. 1,2 In fact, CKD patients have better outcomes when evidencebased therapy is adopted. 2 Analysis of data from large clinical trials demonstrated that the implementation of invasive treatment is associated with better prognosis in patients with endstage renal disease (ESRD) and moderate CKD.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations